Europe on the move : Refugees in the era of the Great War - Žvanko, Ljubov M. 1972-; Žvanko, Ljubov M. 1972-; Gatrell, Peter; Gatrell, Peter (Book collections on Project MUSE., 2019)
Mass population displacement affected millions of Europe's civilians across the different theatres of war in 1914-18. At the end of the war, a senior Red Cross official wrote 'there were refugees everywhere. It was as if the entire world had to move or was waiting to move'. Europe on the move: refugees in the era of the Great War, 1912-23 is the first attempt to understand their experiences as a whole and to establish the political, social and cultural significance and ramifications of the wartime refugee crisis. Drawing on original research by leading specialists from more than a dozen countries, it will become the definitive work on the subject and will appeal to anyone who wishes to understand how governments and public opinion responded to refugees a century ago.